A story of the scoliotic body : reimagining the posture of philosophy with Adriana Cavarero and feminist disability theory - Den Besten, Lauren Marion (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.